Analysis of the Nutrient Content of Liquid Organic Fertilizer (POC) Household Organic Waste in Rimba Jaya Village, Merauke Regency Using the Stacked Bucket Method - Yosefina Mangera; Nurhening Yuni Ekowati (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
The purpose of this study was to analyze the nutrient content of POC produced from household waste using the stacked bucket method. This research was conducted for 3 months from September to November 2020. This research is a descriptive study. The first process is the process of making organic fertilizer from household waste which is fermented in a stacked bucket for 2 months. Leachate from organic waste is dried in the sun for one month or until the leachate is blackish in color and has no more subtle aroma. The finished POC is sampled and tested in the laboratory to determine the content of micro and macro nutrients as well as organic C. To measure the content of macro and micro nutrients, the test material used was Kjeldahl for nitrogen content while P, K, Fe, Mn, Cu, Zn, S, Ca, Mg, Na used spectrometric wet oxidation method and the content of C-organic by spectrophotometric method. The test results showed that the POC of household waste contained 0.08% total N, 0.07% total P, 0.28% total K, 5 ppm total Fe, 0.4 ppm total Mn, 0.0 ppm total Cu, Zn total 0.6 ppm, total S 0.5%, total Ca 165.0 ppm, total Mg 106.9 ppm, total Na 172.7 ppm, organic C 1.06%, and C/N ratio 13.27.